(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Breast cancer is a malignant (cancerous) growth that begins in the tissues of the breast. Cancer is a disease in which abnormal cells grow in an uncontrolled way. Breast cancer is the most common cancer in women. A malignant tumor is a group of cancer cells that can grow into (invade) surrounding tissues or spread (metastasize) to distant areas of the body. Breast Cancer (BC) in women is a major health burden worldwide. It is the most common cause of cancer among women in both high and low income countries. Breast cancer is second only to lung cancer as a cause of cancer related deaths among women. Finally, its aim to investigate the Perception of Women about Breast Cancer in Isiokpo Community of Ikwerre Local Government Area, Rivers State, who were selected randomly. A community-based descriptive cross- sectional study design was carried out among the respondents in Isiokpo Community of Ikwerre Local Government Area, Rivers State. A total of 200 responded were selected. The mean age was 38.3±17.9years. The results revealed that predominant age groups were 20 to 29 years having 57(28.5%). 91(45.5%) of married were the highest respondents in this distribution. 78(39.0%) were respondent whose educational background were secondary levels. 167(83.5%) were house wives. As regards religion, 148(74.0%) were Christians. there was a high level of knowledge on breast cancer with the percentage of 181(90.6%) respondents. that there was a high level of positive perception of breast cancer, 177(88.5%) of respondents. Finally, the results of this work from the research questions, there was high level of knowledge among respondents; the level of perception of breast cancer was significant to a single variable out of many and also this finding revealed that age is one of the variable that influences the knowledge of the respondents about breast cancer.